Simulation analysis of stress-strain performance for a lightweight X-ray pulsar detection telescope frame structure - Qingyong Zhou; Qingyong Zhou; Zhiqiang Huang; Bin Xu; Yaohu Lei; Jianguo Lei; Hang Zhao; Chaojing Ye; Likuan Zhu (Frontiers in Astronomy and Space Sciences)
With the continuous deepening of human exploration of the universe, space telescopes have emerged as pivotal tools for obtaining information about celestial bodies and their evolutionary principles. Structural deformation under load is a critical factor influencing their stable performance. Focusing on the safety design issues faced by the lens frame structure of a pulsar detection telescope independently designed by the research group during space operation, this paper constructed a simulation model using Altair Inspire software. Using titanium alloy (Ti-6Al-4V) as the material and setting fixed constraint boundary conditions, it simulates two types of load conditions: impact forces (200–800 N) generated by object collisions and the torques (30–100 N m) possibly incurred during the installation process, and conducts relevant performance simulation analyses. The results showed that the most vulnerable areas of the component were the lens-protecting fillet regions near the central disk and the outermost circular ring. The structure could withstand a maximum vertical load of approximately 700 N, but the actual operational load should be kept below 250 N. Although torsional loads caused minimal displacement, they induced significant stress concentration at the connections of the crossbeams, indicating that the applied torque should not exceed 50 N m. Measures such as increasing the overall thickness of the component, the cross-sectional area of connecting beams, and the fillet radius at beam corners are proposed solutions to enhance structural strength. The findings provide a theoretical foundation and critical data reference for designing lens frame structures in space detection telescopes.